Resistance of CCA and Boron-Treated Rubberwood Composites Against Termites, Coptotermes curvignathus Holmgren - Ashaari, Zaidon; Moy, C. S.; Sajap, Ahmad Said; Md. Tahir, Paridah (Universiti Putra Malaysia Press, 2003)
A study was conducted to evaluate the resistance of copper-chromium-arsenic (CCA)-and boron-treated rubberwood composites against subterranean termite, Coptotermes curvignathus Holmgren. The materials tested were phenol formaldehyde (PF)-bonded oriented strand board (OSB), melamine urea formaldehyde (MUF)-bonded particleboard and urea formaldehyde (UF)bonded laminated veneer lumber (LVL). Solutions of CCA (0.5-4.0%, w/w of oven dry weight of particles) and boron compounds (boric acid equivalent (BAE) , 0.5 - 1.5% w/w) were separately sprayed onto the furnish during boards manufacturing. The untreated LVL, some of the OSB and particleboard were served as control for comparing purposes. Test blocks, 25 mm x 25 mm x 12 mm were cut from each of the composites and were exposed to 1± 0.05 g termites (10% soldiers and 90% workers) in test bottles for 28 days (ASTM D: 3345-92). Weight losses of the blocks and termite mortality were calculated. OSB treated with 2.0% eGA had the lowest weight loss value (3.0%) compared to those treated with other concentrations (weight loss values = 4.1-6.8%) and those untreated (18.4%). The weight loss for 1.0% and 1.5% BAE-treated OSB blocks were 6.9% and 3.8%, respectively. The resistance of particleboards against termite attack increased by 77% when they were treated with 1% BAE. The mean weight loss value for these boards was 6.13%. Among the untreated rubberwood composites, PF-bonded OSB had the highest resistance against termite attack. UF-bonded LVL was significantly more resistant to termite attack than MUF-bonded particle boards. The weight loss value for the former was 19.3% and the latter was 26.3%. At the end of the test periods, the mortality of termites that were placed together with the treated blocks was 100%, whereas for those placed together with the untreated composites and solid rubberwood, the mortality ranged from 0-16%.